2020
DOI: 10.1128/msphere.00481-19
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic Patterns in Members of Globally Distributed and Dominant Taxa Found in Port Microbial Communities

Abstract: We conducted a global characterization of the microbial communities of shipping ports to serve as a novel system to investigate microbial biogeography. The community structures of port microbes from marine and freshwater habitats house relatively similar phyla, despite spanning large spatial scales. As part of this project, we collected 1,218 surface water samples from 604 locations across eight countries and three continents to catalogue a total of 20 shipping ports distributed across the East and West Coast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In practice, ML can perform surprisingly well on datasets that are sampled from and represent messy real-world systems, such as the human body, soil, and water [48] , [49] , [50] and demonstrates superiority over traditional multivariate statistics in analyzing metagenomic data. In addition to these benchmarks, there is an increase in the development of microbiome-specific 'pipelines' that have user-friendly ML implementation and can be accessed through web-interfaces, the statistical compute language R [51] , or Python [52] .…”
Section: Advantages Of Machine Learning Vs Classical Statistics For mentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, ML can perform surprisingly well on datasets that are sampled from and represent messy real-world systems, such as the human body, soil, and water [48] , [49] , [50] and demonstrates superiority over traditional multivariate statistics in analyzing metagenomic data. In addition to these benchmarks, there is an increase in the development of microbiome-specific 'pipelines' that have user-friendly ML implementation and can be accessed through web-interfaces, the statistical compute language R [51] , or Python [52] .…”
Section: Advantages Of Machine Learning Vs Classical Statistics For mentioning
confidence: 99%
“…These studies used hierarchical clustering and non-metric multidimensional scaling (NMDS) to differentiate groups. More recently, SML has been applied to determining the geographic source of an ocean water sample based on the microbial community [50] . Ghannam et al (2020) [50] demonstrated that RF could be used to accurately differentiate the location of sampling of water from 20 different locations.…”
Section: Optimizing Model Construction and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, higher tax ranks can be used, which are more likely to be found in various areas. Ghannam et al (2020) , for instance, used phyla to differentiate geographic locations on global scale. In our spatially restricted samples the phylum rank also achieved 76.9% mean balanced accuracy, which is still well above coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…Fingerprints related to community-shaping drivers are revealed by performing unsupervised classification, whereas specific influences can be targeted by the application of supervised machine learning. In microbiological studies, RF has been deployed to predict various geochemical features as well as to detect oil spills ( Smith et al, 2015 ) and to localize the geographic origin of port water across three continents based on dominant bacterial phyla ( Ghannam et al, 2020 ). Moitinho-Silva et al (2017) used RF among other classifiers to separate between sponges of high and low microbial abundance.…”
Section: Introductionmentioning
confidence: 99%